On the emergence of the L1 research field: A comparative study of PhD abstracts in the Nordic countries 2000–2017 - Holmberg, Per; Krogh, Ellen; Nordenstam, Anna; Penne, Sylvi; Skarstein, Dag; Karlskov Skyggebjerg, Anna; Tainio, Liisa; Heilä-Ylikallio, Ria (L1-Educational Studies in Language and Literature, 2019)
Research of L1 education is recently established in the Nordic countries. Since the turn of the century we have seen the emergence of national and Nordic research networks, conference and publication series, research programs, and the designation of positions as professors and associate professors. Stud-ies of Nordic L1 research have taken stock of the disciplinary sub fields, but empirical studies of the L1 school subject as a unitary field are still in demand. The aim of this study is to investigate the emergence of Nordic L1 research and its present profile(s) through PhD research. The present study examines the abstracts of Danish, Finnish, Norwegian and Swedish L1 PhD dissertations defended between 2000 and 2017. The results point to a growing field. A general observation is that the research focuses on reading and writing, whereas oral and aesthetical expressions are minor topics. Another result is a set of national differences which are related to governmental policy documents and school curricula. Further, the re-search has become more internationally oriented during recent years. The L1 research is characterized as a professionalized region (Bernstein, 2003) with strong didactization (Ongstad, 2004), and a potential for powerful disciplinary knowledge (Lambert, 2017).